2021
DOI: 10.1177/08862605211044101
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Consent Across Diverse Behaviors and Contexts: Gender Differences and Nonconsensual Sexual Experiences

Abstract: Sexual consent refers to people’s internal willingness to engage in sexual activity with another person—as well as their external communication of that willingness. Internal and external sexual consent can vary by type of sexual behavior; however, previous research on sexual consent has primarily only assessed “typical” sexual behaviors such as genital touching, oral sex, and vaginal–penile sex without providing further context or acknowledging people’s sexual diversity. Therefore, we provided an initial accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It has been suggested that victims prefer the label “sexual assault” to the label “rape” because of the negative societal connotations attached to rape victims. An alternative explanation could be that due to widely shared stereotypes about rape, participants may have been less sure about whether their experience matched the specific characteristics of rape, even though they recognized it as a sexual assault (Hirsch et al, 2019; Temkin & Krahé, 2008; Willis & Smith, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that victims prefer the label “sexual assault” to the label “rape” because of the negative societal connotations attached to rape victims. An alternative explanation could be that due to widely shared stereotypes about rape, participants may have been less sure about whether their experience matched the specific characteristics of rape, even though they recognized it as a sexual assault (Hirsch et al, 2019; Temkin & Krahé, 2008; Willis & Smith, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Inasmuch as entertainment media can influence consumers' beliefs about gender, consumers' own gender identity may also influence their beliefs about sexual consent and how they interpret entertainment media that depict consent. For this particular study, perhaps the most notable difference between men and women is the greater rate of sexual victimization for women (Willis & Smith, 2022). As a result, women have been socialized to take a more defensive approach to sexual activity (Humphreys, 2007).…”
Section: Sexual Script Theorymentioning
confidence: 93%
“…Sexual beliefs related to the importance of sex in life and of pleasure in sex were associated with self-perception of loss of sexual control among both Cape Verdean women and men. Previous work has acknowledged that a diminished sense of sexual control may be related to more sexual compliance, that is, a willingness to engage in unwanted sex, for a variety of motives and with a variety of consequences, from emotional reactions to sexual risk-taking, and sexual violence (Impett and Peplau 2003;Willis and Smith 2021). In this line, our result seems to support that giving too much importance to sexual life may compromise societal roles, as it may be related to less sexual control or a perceived perception of more social loss of control.…”
Section: Contributions From Applying An Intersectionality Lens To Sex...mentioning
confidence: 99%